SOUTH AFRICAN IRON AND STEEL INDUSTRIAL EVOLUTION: AN INDUSTRIAL ENGINEERING PERSPECTIVE - Richmore Aron Dondofema; Stephen Matope; Guven Akdogan (South African Journal of Industrial Engineering, 2017)
The paper focuses on the evolution of the South African iron and steel industry from the industrial engineering perspective. The earliest ironmaking in South Africa dates to the fifth century CE; but the major evolution of the industry began in 1882 and, by the year 1934, steel production from native ore was in full swing. The study highlights the major developments in South Africa’s iron and steel industry, and ends by exploring the extent of the application of industrial engineering techniques to published research into the steel industry.